2008
DOI: 10.3747/co.v15i4.260
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact on Families When a Child Is Diagnosed with Cancer

Abstract: ObjectiveIn a study conducted in New Brunswick and Newfoundland and Labrador, we examined the economic impact on families caring for a child with cancer. MethodsWe undertook semi-structured interviews with 28 French and English families with a child diagnosed with cancer in the last 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 13 publications
5
91
0
Order By: Relevance
“…The non-significant gender differences in this study are of interest since previous studies with shorter follow-up periods have reported differences between mothers and fathers [6][7][8]. With a long-term perspective applied, no such differences were observed.…”
Section: Interpretation Of Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…The non-significant gender differences in this study are of interest since previous studies with shorter follow-up periods have reported differences between mothers and fathers [6][7][8]. With a long-term perspective applied, no such differences were observed.…”
Section: Interpretation Of Resultsmentioning
confidence: 50%
“…A substantial number of parents of children diagnosed with cancer experience significant occupational and financial consequences including employment and income loss, affected work ability, reduced work hours, and sick leave, both during and after treatment completion [3,4]. The impact on parental income, employment and sick leave is greatest during treatment and the effect on employment and earnings is greater among mothers than fathers [3,[5][6][7][8]. There is a lack of longitudinal studies with long-term follow-up on the impact of childhood cancer on parents' work situation.…”
Section: Original Articlementioning
confidence: 99%
“…Long treatment and care of cancer in child result in family economic factors [4], other impacts felt by child and parents that depression and anxiety [5,6]. Mothers reported significantly higher levels of stress than fathers (p <0.001) [7].…”
Section: Introductionmentioning
confidence: 99%
“…can have their access to this tertiary health service facilitated whereas those coming from intermediate and far cities face difficulty accessing care and not return to the service with the ideal frequency due to the distance (6) and financial difficulties (19) , which may interfere on the …”
Section: Discussionmentioning
confidence: 99%
“…Because of this hospital's high technology resources, it attracts patients from surrounding cities and different regions of Brazil, not always within its scope area. This characteristic can hinder the follow-up of children and adolescents of families living outside the city (5) of Ribeirão Preto and also limit the supply of other types of important care procedures, such as home visits to monitor the child and family financial aid for the family to commute to the treatment center (6) , cooperation with the family support network, and proximity to the child's school (7) , among others. …”
Section: Introductionmentioning
confidence: 99%